N-3 PUFA Prevent Oxidative Stress in a Rat Model of Beta-Amyloid-Induced Toxicity - Maria Grazia Morgese; Stefania Schiavone; Maria Bove; Anna Laura Colia; Stefania Dimonte; Paolo Tucci; Luigia Trabace (MDPI AG, 2021)
Polyunsaturated fatty acids (PUFA) are involved in brain disorders associated to amyloid beta (Aβ) toxicity for which oxidative stress, neurochemical dysfunctions, and neuroinflammation are underlying mechanisms. Here, mechanisms through which lifelong exposure to n-3 PUFA-enriched or n-6/n-3 balanced diets could elicit a protective role in a rat model of Aβ-induced toxicity were investigated. To this aim, we quantified hippocampal reactive oxygen species (ROS) amount, 8-hydroxy-2'-deoxyguanosine and interleukin-10 levels, NADPH oxidase (NOX) 1, NOX2, superoxide dismutase 1, and glutathione contents, as well as plasmatic malondialdehyde. Moreover, in the same experimental groups, we assessed tryptophan, serotonin, and its turnover, kynurenine, and noradrenaline amounts. Results showed increased hippocampal ROS and NOX2 levels, serotonin turnover, kynurenine, and noradrenaline contents in Aβ-treated rats. Both n-6/n-3 balanced and n-3 PUFA enriched diets reduced ROS production, NOX1 and malondialdehyde levels, serotonin turnover, and kynurenine amount in Aβ-injected rats, while increasing NOX2, superoxide dismutase 1, and serotonin contents. No differences in plasmatic coenzyme Q10, reduced glutathione (GSH) and tryptophan levels were detected among different experimental groups, whereas GSH + oxidized glutathione (GSSG) levels were increased in sham animals fed with n-3 PUFA enriched diet and in Aβ-treated rats exposed to both n-6/n-3 balanced and n-3 enriched diets. In addition, Aβ-induced decrease of interleukin-10 levels was prevented by n-6/n-3 PUFA balanced diet. N-3 PUFA enriched diet further increased interleukin-10 and 8-hydroxy-2'-deoxyguanosine levels. In conclusion, our data highlight the possible neuroprotective role of n-3 PUFA in perturbation of oxidative equilibrium induced by Aβ-administration.